2018
DOI: 10.1186/s12884-018-2093-6
|View full text |Cite
|
Sign up to set email alerts
|

Getting through the day: a pilot qualitative study of U.S. women’s experiences making decisions about anti-nausea medication during pregnancy

Abstract: BackgroundNausea during pregnancy affects 80% of pregnant women and can severely affect women’s functioning and quality of life. Women often have difficulty deciding whether to take anti-nausea medications due to concern about medication risks. This paper foregrounds U.S. women’s voices as they share their experiences making decisions about anti-nausea medication use.MethodsAs a pilot study, we conducted two focus groups including 20 women who had filled at least one prescription for an anti-nausea medication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Women may be reluctant to take, and non-specialist clinicians may be reluctant to prescribe, pharmacological treatments owing to concerns about teratogenic risk. 35,36 Women should be counselled that the benefits of antiemetics outweigh the risks, and that the absolute risk is low. Antiemetics are therefore appropriate and should be offered (see section 6.2.2).…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Women may be reluctant to take, and non-specialist clinicians may be reluctant to prescribe, pharmacological treatments owing to concerns about teratogenic risk. 35,36 Women should be counselled that the benefits of antiemetics outweigh the risks, and that the absolute risk is low. Antiemetics are therefore appropriate and should be offered (see section 6.2.2).…”
Section: Historymentioning
confidence: 99%
“…In areas where ‘acute care at home’ or ‘hospital at home’ services are operating to provide IV treatment in the community, these services can be utilised for IV rehydration at home for women who are unable to maintain hydration orally but who do not have co‐morbidities or complications. Women may be reluctant to take, and non‐specialist clinicians may be reluctant to prescribe, pharmacological treatments owing to concerns about teratogenic risk 35,36 . Women should be counselled that the benefits of antiemetics outweigh the risks, and that the absolute risk is low.…”
Section: How Should Women With Nvp and Hg Be Cared For?mentioning
confidence: 99%
“…It is possible that in the 18 years since the Baggley et al study was published, the use of prescription anti-nausea medications has become more widely considered routine care, consistent with evidence from Schrager and colleagues, 28 who found that the use of several prescription and over-the counter antiemetics has increased over time. Figueroa Gray et al 3 found that pregnant women deciding whether to take prescription anti-nausea medication relied on both the opinions of medical providers and the experiences of friends and family. It is also possible that if participants took medication during a previous pregnancy, that they may have been less likely to seek out feedback on their medication decision for the current pregnancy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…2 Those experiencing nausea and vomiting during pregnancy need to decide if and how to treat their symptoms, weighing the potential impacts of untreated symptoms against the potential risks of a chosen treatment for the pregnant person and fetus. 3,4 A small amount of existing research has explored how pregnant individuals experiencing nausea and vomiting choose whether to use anti-nausea medication, 1,3 and how people may choose to self-treat their nausea and vomiting during pregnancy with cannabis. 5 Cannabis use during pregnancy is increasingly common, 6 and several studies show an association between nausea and vomiting during pregnancy and cannabis use.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant and breast-feeding women are further inclined to become ‘therapeutic orphans’, by their routine exclusion from clinical trials, given the struggle to insure such trials involving pregnant women. Pregnant women are further disadvantaged by having to arduously navigate through multifarious social influences, some losing their autonomy in medical decision making around taking medications or in their choice to participate in a clinical trial during pregnancy 3 4…”
Section: Introductionmentioning
confidence: 99%